Design and Implementation of a Blockchain-based Global Authentication System Using Biometrics and Subscriber Identification Module - Khalili, Navid (Université d'Ottawa / University of Ottawa, 2022)
The digital world tolerates a high volume of information and interactions. Considering the usage of electronic services by authorities, User Authentication (UA) is crucial. Numerous authentication methods are proposed in the literature; yet, identifying users based on their actual identities with the capability of global usage and respecting privacy is under research. By adopting Blockchain technology in the software industry, the record management systems have satisfied properties such as transparency, accountability, anonymity, and attack resiliency. Moreover, Smartphones are powerful devices capable of hosting a Subscriber Identification Module (SIM) Card that secures the execution of processes involving use of sensitive information. A combination of these technologies is the foundation of a strong UA in cyberspace. In this thesis, we propose the design and prototype of Blockchain-based Global Authentication System (BBGAS) that offers a secure, privacy-preserving, and transparent authentication system based on users' biometrics via Smartphones appropriate for service provider applications.
Keywords: Authentication; Electronic Governments; Smart Cities; Biometrics; SIM Card; Blockchain; Smartphones